Children and young people's beliefs about mental health and illness in Indonesia: A qualitative study informed by the Common Sense Model of Self-Regulation. - Helen Brooks; Kirsten Windfuhr; Irmansyah; Benny Prawira; Dyah Afina Desyadi Putriningtyas; Karina Lovell; Susi Rutmalem Bangun; Armaji Kamaludi Syarif; Christa Gumanti Manik; Ira Savitri Tanjun; Soraya Salim; Laoise Renwick; et al. (PLoS ONE)
Background Mental illness is a leading cause of disease burden amongst children and young people (CYP). This is exacerbated in low- and middle-income (LMIC) countries which often have embryonic care structures. Understanding and targeting illness beliefs is a potentially efficacious way of optimising the development of health prevention interventions. These beliefs remain relatively underexplored in CYP in LMIC contexts. Aim: To develop an in-depth understanding of CYPs beliefs about mental health and illness in Indonesia. Methods and findings Semi-structured interviews (n = 43) combined with photo elicitation methodology were undertaken with CYP aged 11-15 from Java, Indonesia. Our sample comprised those living with (n = 19) and without (n = 24) high prevalence mental health conditions, specifically anxiety or depression. Data were analysed using framework analysis, informed by the Common Sense Model of Self-Regulation of Health and Illness. Positive mental health and illness were dichotomised in accounts with mental health typically characterised as an absence of mental disturbance. This contributed to attributions of abnormality and the marginalisation of those with mental illness. Mental illness was conceptualised as a single entity, commonly arising from individual failings. This prompted feelings of self-stigma in those with lived experience of mental illness. Analysis identified marked differences in the perceived time dimensions of positive mental health and illness with mental illness conceived as less transient than episodes of positive mental health. Illness beliefs appeared relatively consistent across the two groups of CYP although some nuanced differences were identified. CYP with anxiety and depression were less likely to believe that mental illness could be diagnosed visually, more likely to uphold multiple causal factors and endorse the potential efficacy of professional input. Conclusions Public health interventions to increase understanding may be necessary to develop healthcare systems to reduce treatment barriers, optimise return on investment and enhance population health effect.